Innovation and control: universities, the knowledge economy and the authoritarian state in China - Barbara Schulte (Taylor & Francis Group, 2019)
Like many other education systems in the world, Chinese education has undergone various reforms in order to adapt to the challenges that are perceived to emanate from the knowledge economy. Central to this transformation is the concept of 'innovation', which is to guide the country on its path from a production economy to a knowledge economy. Chinese policymakers have been targeting the higher education sector both as a motor for innovation and as a realm to be innovated, and have invested heavily in the sector's internationalization, above all in the form of international collaboration and student mobility, affecting higher education and academia worldwide. However, a number of structural and political constraints delimit the directions that innovation can take, both within Chinese education in general and within Chinese higher education. The article takes stock of these constraints and assesses the potential for innovation in Chinese higher education in terms of the underlying school system, exam and recruitment policies, the (re-)organization of universities, as well as the universities' and science system's performance according to indicators of innovation. The article then identifies four 'Chinese innovation dilemmas', that is, educational policies and developments that are to spur innovation but run counter to existing structures and practices of educational, social, and political governance: ideological control versus creativity; state planning versus grassroots innovation; old-boy networks versus anti-corruption; and exam-based student recruitment versus flexible recruitment.